PRODUKSI SEDIAAN KOMBUCHA DARI DAUN PERMOT (Passiflora foetida L) SECARA FERMENTASI - Herwin Herwin; Rachmat Kosman; Iswan Siami (Fakultas Farmasi UMI, 2013)
A research has been done about profit of permot leaves (Passiflora foetida L.) by using culture of kombucha with the aim to know the use of permot leaves (Passiflora foetida L.) as preparation of kombucha in a fermentation. Permot dried leaves boiled in 1000 ml water until boiling then got extract of permot. Extract of permot leaves added with 100 gram glucose and 10% of inoculum kombucha culture then fermented for 5 – 12 days. The results of kombucha preparation from permot leaves then testing with organoleptic, measuring pH and total acid test. Based of the results in preparation kombucha permot leaves (Passiflora foetida L.) showed that the color-test organoleptic with hedonic method was obtained values 2.5, flavor 1.9, and taste 2.4. pH measurement before fermentation is 4 and after that is 3 with total acid of 0.66%. Key Word : Permot Leaves (Passiflora foetida L.), Fermentation, Kombucha of Preparation